2015
DOI: 10.1097/md.0000000000000753
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Subsequent Genitourinary and Gynecologic Cancers Risk

Abstract: Although a relationship between hypertension and the development of renal cancer and other types of cancer have been proposed for decades, the results of epidemiologic studies remain inconclusive. This study was conducted to evaluate the association between hypertension and genitourinary and gynecologic cancers in Taiwan.In this study, we conducted a populated-based retrospective cohort study by using data from the Taiwanese National Health Insurance program. The study period was from 2000 to 2011, and the coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 50 publications
1
35
0
2
Order By: Relevance
“…Furthermore, the NHIRD data have been used for various studies for several years. [ 14 , 15 , 20 25 ] Second, the NHIRD does not contain detailed information regarding such risk factors as body mass index, exercise capacity, dietary habits, alcohol consumption, and smoking, which potentially compromises our findings. [ 3 , 4 ] Discussion regarding impotence remains a sensitive issue in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the NHIRD data have been used for various studies for several years. [ 14 , 15 , 20 25 ] Second, the NHIRD does not contain detailed information regarding such risk factors as body mass index, exercise capacity, dietary habits, alcohol consumption, and smoking, which potentially compromises our findings. [ 3 , 4 ] Discussion regarding impotence remains a sensitive issue in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…The patients in the ED and non-ED groups were followed until they were diagnosed with osteoporosis, withdrawal from insurance or end of follow-up. Baseline comorbidities (ICD-9-CM codes are provided in Supplementary Table S1) [ 15 , 22 25 ] were hypertension, DM, hyperlipidemia, CKD, chronic liver disease, chronic pulmonary disease, stroke, hyperthyroidism, and hyperparathyroidism before the index date. The Charlson comorbidity index (CCI) scores, categorized into 4 levels (0, 1–2, 3–4 and ≥5), were used for assessing the severity of comorbidities.…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, Cancer Information Service, National Cancer Center, Japan, estimated that the total incidence of kidney cancer (including upper tract urothelial cancer) was 24 865 (16 610 male and 8 255 female) . Growing evidence suggests that stress‐related risk factors—eg, smoking, obesity, and hypertension—contribute to the risk of renal cell cancer . However, very little is known of the role that stress plays in the risk of renal cell cancer, and the association between hypertension and the risk of renal cell cancer has been previously undocumented in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Supportive evidence includes the ME-Can cohort study, which showed that elevated BMI, BP and triglyceride levels were associated with an increased risk of cervical cancer besides high glucose, which was a risk factor among women 70 years old and above37; a meta-analysis found a modest positive association of BMI with cervical cancer30; a prospective study from China found that there was an increased risk of persistent HPV infection and an increased risk of incident HPV infection among obese women; however, no association was found with hyperglycaemia or HT 38. Negative pieces of evidence are an observational prospective cohort study from China found significant decreased standardised incidence ratios for cervical cancer among patients with type 2 DM,39 and a prospective cohort study from Taiwan failed to show an increased risk of cervical cancer among hypertensive individuals 40…”
Section: Discussionmentioning
confidence: 99%